A New Handbook of Political science - GOODIN, Robert E (Oxford University Press, 1996)
With contributions by 42 of the best political scientists worldwide, A New Handbook of Political Science analyzes the progress made in political science over the past twenty years in the context of historical trends in the field. International in its scope and systematic in its coverage, this comprehensive volume will be an essential reference book for political scientists and those who track their work. It is the ideal companion for all who intend to follow political science into the next century.